2020
DOI: 10.1051/e3sconf/202020505016
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of thermo-mechanical response of a geothermal pile through a small-scale physical modelling

Abstract: Energy piles have been used around the world to harvest geothermal energy to heat and cool residential and commercial buildings. In order to design energy geo-structures, thermo-mechanical response of the geothermal pile must be carefully understood. In this paper, a small scale physical model is designed and a series of heating thermal cycles with various vertical mechanical loads are performed. The instrumented pile is installed inside a dry sand bed. Changes in pile head displacement, shaft strains and pile… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
2
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 21 publications
0
5
0
Order By: Relevance
“…Some researchers directed their effort to assess the thermal efficiency of energy piles and to reveal the involved parameters [6][7][8][9][10]. Some researchers investigated the behavior of energy piles using field scale tests [11][12][13][14][15] or model scale tests [16][17][18][19][20][21][22][23]. Sutman et al [24] also studied the effect of end and head restraint condition on the behavior of energy piles using a field test and reported that the thermo-mechanical behavior of energy piles, that is to say, axial displacements, mobilized shaft resistance and thermal stresses are highly associated with the restraint conditions on both ends of the pile.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Some researchers directed their effort to assess the thermal efficiency of energy piles and to reveal the involved parameters [6][7][8][9][10]. Some researchers investigated the behavior of energy piles using field scale tests [11][12][13][14][15] or model scale tests [16][17][18][19][20][21][22][23]. Sutman et al [24] also studied the effect of end and head restraint condition on the behavior of energy piles using a field test and reported that the thermo-mechanical behavior of energy piles, that is to say, axial displacements, mobilized shaft resistance and thermal stresses are highly associated with the restraint conditions on both ends of the pile.…”
Section: Introductionmentioning
confidence: 99%
“…They stipulated that piled rafts undergo smaller tilts under unsymmetrical thermal loads. Senejani et al [16] investigated thermo-mechanical behavior of a single energy pile using a small-scale physical model setup. They reported a reduction in elastic response of the soil during longer thermal cycles.…”
Section: Introductionmentioning
confidence: 99%
“…The behaviour of the soil‐energy pile‐structure system under normal operating conditions—that is, subjected to thermal cycles—has been mainly investigated experimentally by laboratory or field tests on instrumented energy piles 22–35 …”
Section: Introductionmentioning
confidence: 99%
“…21 The behaviour of the soil-energy pile-structure system under normal operating conditions-that is, subjected to thermal cycles-has been mainly investigated experimentally by laboratory or field tests on instrumented energy piles. [22][23][24][25][26][27][28][29][30][31][32][33][34][35] An experimental study conducted on small scale models tested in a geotechnical centrifuge at 40g 36 has shown that an energy pile installed in lightly overconsolidated (OC) clay accumulates larger irreversible settlements if compared to a pile in heavily overconsolidated clay. In a series of small-scale pile loading tests at 1 g, Wu et al 37 observed that a single energy pile subjected to heating and cooling cycles undergoes an accumulation of irreversible axial displacements at the pile head, progressing at an almost constant rate, while the soil experiences an increase and decrease of pore water pressures during heating and cooling stages, respectively, with progressively smaller increments of excess pore water pressure as the number of thermal cycles increases.…”
mentioning
confidence: 99%
“…The thermal resistance of the side changed its direction more with thermomechanical loading than solely with thermal loading (Sutman et al, 2019;Sutman et al, 2015;Sutman et al, 2017). In another study, Senjani et al (2020) modeled a pile in dry sand and concluded that reversible settlements occur when the load is less than 20% of the bearing capacity of the geothermal pile, but that irreversible displacement occurs when they exceed this value (Senejani et al, 2020). Despite many studies performed on analyzing the load transfer mechanism in energy piles under thermomechanical loading, only a few studies repeat the same experiments with only varying the boundary conditions at the pile head and pile base to analyze the role of relative density on the thermomechanical stress along the pile under variable pile head and base conditions.…”
Section: Introductionmentioning
confidence: 99%